MOLECULAR DOCKING ANALYSIS OF THE BIOACTIVE COMPOUND EMODIN WITH VEGFR2 IN CERVICAL CANCER - Innayah Rania Farzana; Rara Inggarsih; Ziske Maritska; Ayeshah Augusta Rosdah; Soilia Fertilita (Jurnal Kedokteran dan Kesehatan : Publikasi Ilmiah Fakultas Kedokteran Universitas Sriwijaya, 2026)
Cervical cancer remains a leading cause of cancer-related mortality among women and represents the third most common cancer globally. Elevated VEGF expression in cervical cancer is associated with poor prognosis, highlighting the relevance of anti-VEGF therapeutic strategies. Several studies have shown that emodin, a natural anthraquinone derivative mainly isolated from Rheum palmatum, inhibits VEGF-stimulated proliferation, migration, and formation of endothelial cells. This study aims to characterize the interaction between emodin and the VEGF receptor in cervical cancer through in silico molecular docking. The workflow included preparation of the compound structure, preparation of the target protein structure, docking protocol validation, and docking of the compound to the receptor. Lower binding energy reflects a stronger and more stable interaction. The docking analysis showed that the emodin–VEGFR2 complex exhibits a binding energy of −7.78 kcal/mol, forming three hydrogen bonds with GLU915, CYS917, and LEU838, as well as three van der Waals interactions with PHE916, GLY920, and VAL846. These findings demonstrate a stable interaction between emodin and VEGFR2 and suggest its potential as a lead compound for further development of VEGFR2-targeted inhibitors, underscoring the need for subsequent in vitro and in vivo validation.